Study of clinical and endoscopic profile of dyspepsia and upper gastrointestinal bleed - Rajender, Akash; Choudhary, Priyanka; Mathur, Saumya; Bhargava, Rajat; Upadhyay, Shalini; Nepalia, Subhash (International Journal of Advances in Medicine, 2019)
Background: Upper gastrointestinal bleed (UGIB) and dyspepsia are the commonest indications for an upper GI endoscopy (UGIE), which has the potential to provide both diagnostic and therapeutic intervention. Alarm symptoms in patients with dyspepsia need proper evaluation. Methods: In an observational hospital-based study, 5117 patient undergoing upper GI endoscopy were evaluated at Mahatma Gandhi Medical College and Hospital, Jaipur, Rajasthan, India. Detailed clinical and endoscopic profile was evaluated for subjects with dyspepsia and UGIB. Statistical analysis was done using SPSS version 21.0. Results: Dyspepsia (2887, 56.41%) followed by upper GI bleed (1124, 21.97%) were the most common indications for UGIE. In subjects presenting with UGIB, most patients had both hematemesis with Malena (48.04%), 48.93% were chronic alcoholics and nearly one fourth (26.96%) were on NSAIDS. Variceal bleeding (52.94%), followed by peptic ulcer bleed (13.43%) were the most common causes of bleed. In subjects undergoing UGIE for dyspepsia, 37.41% revealed no endoscopic lesion followed by gastro-duodenitis (25.01%). Peptic ulcer was cause of dyspepsia in 18.05% and was significantly more in those with alarm symptoms (<0.001). Alarm symptoms in dyspepsia has a significant high likelihood of finding a malignant lesion on endoscopic evaluation (p 0.013). Conclusions: Variceal bleed is the most common cause of UGIB in the adult Indian population. In patients with dyspepsia, presence of alarm symptoms is significantly associated with organic lesion on endoscopy. Although the incidence of malignancy is low, endoscopy in more than 50years subjects presenting with dyspepsia may help in early diagnosis and reducing morbidity.